Disability and pain after lumbar surgery-group-based trajectory analysis. - Konsta Koivunen; Jari Arokoski; Sara Widbom-Kolhanen; Katri Pernaa; Juhani Juhola; Mikhail Saltychev (PLoS ONE)
Background and aims Previous studies in lumbar spine surgery have mainly studied functioning and pain by comparing average scores from Patient Reported Outcome Measures (PROMs) at different time points. Less is known about these changes in different subgroups. It is self-evident that, while most patients may demonstrate trajectories of these changes close to the average one, some groups may follow more or less different trends. Also, it is unclear which preoperative factors may affect the probability of being classified into groups with different development trajectories of surgical outcome. The objective of this study was to identify groups exhibiting distinct trajectories within the broader cohort of patients undergoing lumbar spine surgery and to determine whether certain factors may be associated with a probability of being classified into a particular group. Methods This was a register-based study of 1,451 patients undergoing lumbar spine surgery. The group-based trajectory analysis was used separately for leg pain, for back pain, and for functioning. The probability of group membership was calculated based on sex, age, leg and back pain duration before surgery, and obesity. Results Two kinds of group-based trajectories were identified for each of three-factor variables: a long-term and a short-term improvement group. Sex and age were not associated with being classified into short-term improvement groups, but obesity was associated for all three-factor variables with relative risk ratios (RRR) varying from 1.26 (95% CI 1.02 to 1.56) to 1.45 (95% CI 1.10 to 1.90). Preoperative leg and back pain duration was significantly associated solely with back pain severity with an RRR of 1.28 (95% CI 1.01 to 1.61). Conclusions The results of this study suggest that most of the patients may experience pain relief and improved functioning within three months after lumbar surgery, and this effect may last, at least, for two years. Higher BMI and worse preoperative pain and disability were associated with the inferior outcome of surgery. When considering surgery, planning pre- and postoperative rehabilitation, or forecasting the use of pain medications, a higher probability of worse outcome could be expected for overweight and initially more painful patients with higher level of disability.